Fifty years of failure : employment services for disabled people in the UK - Hyde, Mark [Verfasser] (My University, 1996)
"The 1944 Disabled Persons (Employment) Act introduced a range of programmes to help disabled people find and keep paid work but, until recently, little was known about their effectiveness. This paper reports the findings of a survey of economically active disabled people and shows that their feelings about statutory employment services are mixed. A small majority expressed satisfaction, but a significant minority reported negative experiences. The state's employment programmes for disabled people frequently ignore 'felt needs' and some services are segregated, leading to problems such as 'stigma'. The paper concludes by reflecting on policy to improve services and argues that integration into 'improved' mainstream areas of provision is the best way forward." (author's abstract, IAB-Doku) ((en)) Der Beitrag untersucht die Wirksamkeit der Behindertenpolitik in Grossbritannien. Insbesondere wird auf die Massnahmen zur beruflichen Integration eingegangen. Eine knappe Mehrheit der befragten Behinderten drückten ihre Zufriedenheit mit der Arbeitsverwaltung aus. Eine bedeutsame Minderheit berichtet aber auch von negativen Erfahrungen. (IAB)
Keywords: G 1.1 Soziostrukturelle & Ökonomische Entwicklungen; G 2.4 Sozialer Wandel; S 2.3 Berufsbildungspolitik; G 1.2.2.3 Beschäftigungsformen; P 1.6 Behinderte; G 1.3.3.4 Wiedereingliederung; G 1.2 Arbeitsmarkt; I 2.2.1 Westeuropa; Behindertenpolitik; Programm; Erfolgskontrolle; Menschen mit Behinderung; Stigmatisierung; Behindertenwerkstätte; Rehabilitation; Einstellung; Arbeitsverwaltung; Quantitative Angaben; Großbritannien